Effect of age and physical exercise on amplitude modulation detection thresholds - DASHIKA G.M; NIKHITHA B THERUVAN; JAYASHREE S BHAT; PITCHAI MUTHU ARIVUDAI NAMBI (International Journal of Pharma and Bio Sciences, 2016)
The present study aimed to investigate the effect of aging on amplitude modulation detection thresholds (MDT) and also to investigate the effect of physical exercise on MDT in older adults. Thirty six individuals were divided into three groups with twelve participants in each group. Group1 consisted of younger adults (YA), group2 consisted older adults who underwent systematic physical exercise program (OA-E) and group3 consisted of older adults (OA) who did not undergo physical exercise. All the participants had normal hearing.MDT was measured at two carrier frequencies (500Hz and 4000Hz) and four modulation frequencies (8Hz, 16Hz, 32Hz and 64Hz). MDT of YA was significantly better than the OA-E and OA suggesting that,despite having normal hearing sensitivity, temporal processing is poor in older adults. Physical exercise had positive effect on MDT at 16Hz, 32Hz and 64Hz modulation frequency for 500Hz carrier frequency indicating that, physical exercise possibly improves the temporal.